E-ECLAB inventory system for FKP ( software development ) - Nursyafinaz, Jaafar (2013)
This thesis describes about the Electronic Component Laboratory services or EECLAB. E-ECLAB is a one of the real time management of inventory component in catalog which is consistent with the aim of this project to facilitate inventory management system in term of requisition of component in laboratory. Where EECLAB support updating inventory information for all components, monitoring inventory depletion and importing and exporting inventory information to and from external system of record. The interfaces are design by using Visual Basic (VB), where VB a productively building type-safe and object-oriented applications while the database using Microsoft Office Access. There are several analyses has been made by identify the requirement specification, design the interface, implementation or debug the code, testing it with by releasing the application, make the installation after publish the testing part had running smoothly and lastly maintaining and enhancing the application. These applications are very friendly user, where user can track their requisition by scan the bar code given. The administrator that handles this inventory have easy way to update stock and approval the requisition sent by user. With this application, the inventory in laboratory will become more systematic and more accurate.